Peroxisome Proliferator-Activated Receptors Regulate Hepatic Immunity and Assist in the Treatment of Primary Biliary Cholangitis - Wang, Chang; Shi, Ying; Wang, Xiaomei; Ma, Heming; Liu, Quan; Gao, Yanhang; Niu, Junqi (Frontiers in Immunology, 2022)
Fibrates, which are agonists of peroxisome proliferator-activated receptor alpha, have received increasing attention in the treatment of primary biliary cholangitis. Reduced alkaline phosphatase levels and improved clinical outcomes were observed in patients with primary biliary cholangitis with an inadequate response to ursodeoxycholic acid (UDCA) monotherapy when treated with bezafibrate or fenofibrate combined with UDCA. In contrast to obeticholic acid, which exacerbates pruritus in patients, fibrates have been shown to relieve pruritus. Clinical trial outcomes show potential for the treatment of primary biliary cholangitis by targeting peroxisome proliferator-activated receptors. It is currently agreed that primary biliary cholangitis is an autoimmune-mediated cholestatic liver disease, and peroxisome proliferator-activated receptor is a nuclear receptor that regulates the functions of multiple immune cells, thus playing an important role in regulating innate and adaptive immunity. Therefore, this review focuses on the immune disorder of primary biliary cholangitis and summarizes the regulation of hepatic immunity when peroxisome proliferator-activated receptors are targeted for treating primary biliary cholangitis.